2023
DOI: 10.1177/15385744231154990
|View full text |Cite
|
Sign up to set email alerts
|

Medusa’s Wrath: Bleeding Giant Scalp Arteriovenous Malformation in an Adult: A Case Report

Abstract: Background Scalp arteriovenous malformation (AVM) is a rare congenital disease that may present with massive bleeding. To date, surgical excision remains the definitive management. However, the procedure could lead to intraoperative bleeding due to the tumor’s high blood flow and complex vascularity. Case Report A 49-year old Filipino male presented with a bleeding giant scalp AVM. Computed tomographic scan and duplex studies showed multiple feeding vessels with turbulent flow arising primarily from the right … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…The most recently published case report of scalp AVM by Briones et al featured a 49-year-old man who presented to the ER with a giant AVM of the right temporal area accompanied by a large amount of bleeding [ 10 ]. The preoperative hemoglobin concentration was 6 g/dL which required a preoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The most recently published case report of scalp AVM by Briones et al featured a 49-year-old man who presented to the ER with a giant AVM of the right temporal area accompanied by a large amount of bleeding [ 10 ]. The preoperative hemoglobin concentration was 6 g/dL which required a preoperative blood transfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Because of the differences in high shunt flow, vascular anatomy, and cosmetic deformities, treatment strategies have been documented to be case-dependent, including surgical excision, ligation, or endovascular embolization [2]. Several studies demonstrated different presentations, diagnostic methods, and management options [10,[12][13][14]. However, scalp AVMs remain a rare entity in need of further neurosurgical focus.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation